An Analogue-Difference Method and Application to Induction Motor Models (Journal of Nonlinear Modeling and Analysis, 2024)
The paper established a so-called analogue-difference method (ADM) to compute the numerical solutions for boundary value problems of higher-order differential equations, which can be a fundamental method and performsmuch better than the finite difference method (FDM), even for second-orderboundary value problems. Numerical examples and results illustrate the simplicity, efficiency and applicability of the method, which also show that theproposed method has obvious advantages over the methods presented by recentstate-of-the-art work for induction motor models.